Dynamically reconfiguration architecture for embedded systems using Kaffe - Dung, Vu Quang; Ha, Nguyen Viet; Khanh, To Van (VNU Journal of Science: Mathematics - Physics, 2007)
In designing embedded systems, the exploration and synthesis of diíĩerent design aỉtematives and co-verification of a specific implementation are the most demanding tasks. Kaffe, an open-source technology, proviđes a platform for building a runtime environment and integrating diíĩerent design methodologies. Integrating Kaffe into embedded systems is the cornerstone o f java-like technologies, allowing possibilities such as the development of portable programs on mobile devices. In this paper, vve introduce a co-design environment based on Kaffe vvhich supports the speciíication and prototyping o f dynamicalỉy reconíigurable embedded syslems. Keyvvords: Embedded systems, Kaffe Virtual Machine (KVM), real-time systems, ARM, Hardware-Software co-design, Java Native Interface, Kaíĩe Native Interíace